Central Statistical Office as a source of information that is relevant in determining the state of the public finances of the Republic of Poland. The financial management of the Central Statistical Office - Wojciech Bożek (Prawo Budżetowe Państwa i Samorządu)
In the elaboration the author discussed the meaning of the public statistics in public finances, the structure and the financial activity of the Central Statistical Office (CSO) and other units of public sector, which is related with it. Besides, the author indicates example of legal solutions in the Polish order financial which underlines the importance and actualness of undertaken subject matter. Also, the author underlines the meaning of the public statistics in the process of the efficient financial management public and conducts of the transparent economy with public measures. The author constates that the catalogue of tasks of CSO, from the perspective of public finance, is extensive and dynamic.